Studies of ethylene/1-hexene copolymerization over zirconocene catalyst supported on MAO-modified MgCl2(THF)2. The effect of copolymerization conditions on the intermolecular heterogeneity of copolymers - Białek, M.; Czaja, K.; Sacher-Majewska, B. (Polimery, 2022)
Composition of catalytic system and copolymerization reaction conditions influence on heterogeneity of ethylene)1-hexene copolymers obtained over MgCl2(THF)(2)/MAO/Cp2ZrCl2/MAO catalyst was studied. One of the DSC techniques, i.e. successive self-nucleation/annealing (SSA) method allowing separation of the polymer into fractions with differing chemical composition in result of alternating crystallization and melting cycles was applied. It was found that the intermolecular heterogeneity exists inside all studied samples irrespective of the reaction conditions (temperature and time) and the catalyst composition (Al/Zr molar ratio). It was also confirmed that catalyst composition has a considerably greater impact on heterogeneity of the copolymers as compared with copolymerization conditions, which apart from the first period of the reaction - do not exert significant influence on this parameter of copolymer structure.